Exploring Students' School Well-Being in Private Islamic Boarding School: A Case Study - Thoyibah, Firda Amalia; Wahdah, Nurul; Surawan, Surawan (International Journal of Education and Teaching Zone, 2025)
Student well-being has become an increasingly critical concern amid demanding curricula and intense academic competition, particularly in boarding schools. However, this aspect is often overlooked as schools tend to prioritize academic achievement over holistic development. This study aims to examine the level of student well-being at Hasanka Islamic Boarding School in Palangka Raya using a four-dimensional framework encompassing having, loving, being, and health. Employing a mixed-methods approach with an explanatory sequential design, the quantitative phase collected data from 123 students selected through proportionate stratified random sampling based on the Slovin formula. The qualitative phase involved interviews, observations, and documentation to validate and enrich the survey findings. Results revealed that most students reported a moderate level of school well-being. The having and being dimensions achieved the highest mean scores, underscoring the importance of adequate facilities and opportunities for self-fulfillment in fostering well-being. In contrast, the loving and health dimensions scored lowest, indicating that social connectedness and physical-mental health remain vulnerable aspects in boarding school environments characterized by dense and competitive curricula. The findings highlight the necessity for integrated school strategies that balance academic rigor with students’ physical health, mental resilience, and social support systems to promote holistic well-being within the school context at school level, especially in Indonesia.